2007
DOI: 10.1007/s11069-007-9120-7
|View full text |Cite
|
Sign up to set email alerts
|

Alert system to mitigate tephra fallout hazards at Mt. Etna Volcano, Italy

Abstract: Volcanic eruptions may create a wide range of risks in inhabited areas and, as a consequence, major economic damage to the surrounding territory. An example of volcanic hazard was given between 1998 and 2001 by Mt. Etna volcano, in Italy, with its frequent paroxysmal explosive activity that caused more than a hundred fire-fountain episodes. In the period January-June 2000, in particular, 64 lava fountains took place at the Southeast Crater. During the most intense explosive phase of each episode, a sustained c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 18 publications
0
36
0
Order By: Relevance
“…2001 and 2002-2003) and its characterization is often difficult due to the high variability of eruptive phenomena and meteorological conditions that influence and scatter the fallout sedimentation (Andronico et al, 2008;Scollo et al, 2007). However, constant monitoring of the explosive activity at Etna has been performed during the last two decades (Alparone et al, 2007;Andronico et al, 2009). An exceptional amount of data was collected thanks to many field surveys that were carried out at the end of explosive activities (e.g.…”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 99%
“…2001 and 2002-2003) and its characterization is often difficult due to the high variability of eruptive phenomena and meteorological conditions that influence and scatter the fallout sedimentation (Andronico et al, 2008;Scollo et al, 2007). However, constant monitoring of the explosive activity at Etna has been performed during the last two decades (Alparone et al, 2007;Andronico et al, 2009). An exceptional amount of data was collected thanks to many field surveys that were carried out at the end of explosive activities (e.g.…”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 99%
“…1). Furthermore, for the sake of comparison, we also applied detection methods based on fixed thresholds of seismic and infrasonic RMS (see Alparone et al, 2007a) and reported the results in Fig. 7b and c, respectively.…”
Section: Investigation On Detection Thresholdmentioning
confidence: 99%
“…Surveillance cameras are very useful for detecting the height of eruption columns and analyze the style of explosive activity. Analysis of these images is used routinely at INGV-CT during Etna explosive activities (Alparone et al, 2007;Andronico et al, 2008a, b;Scollo et al, 2007).…”
Section: Monitoring Systemmentioning
confidence: 99%
“…The constrain of these parameters is usually given by analysis of field data collected during the monitoring activities of INGV-CT (Alparone et al, 2007;Andronico et al, 2009). However, two different typologies of explosive activity have been identified at Etna (Scollo, 2006): one producing strong and short-lasting plumes and another producing weak and long-lasting plume.…”
Section: Eruptive Scenariosmentioning
confidence: 99%